2019
DOI: 10.1039/c9re00142e
|View full text |Cite
|
Sign up to set email alerts
|

Continuous flow synthesis of ordered porous materials: from zeolites to metal–organic frameworks and mesoporous silica

Abstract: Herein we review the concepts, challenges and recent developments on the continuous flow synthesis of ordered porous materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 214 publications
0
45
0
Order By: Relevance
“…Another key advantage of flow processing is that precise and reproducible access to well‐defined (typically very short) reaction times can be achieved by varying the respective reactor volumes or flow rates . Recently, it has been demonstrated that MOFs can be prepared with controlled particle size using flow technology . Specifically, ZIF‐8 has been produced in flow using a variety of equipment and procedures .…”
Section: Figurementioning
confidence: 99%
“…Another key advantage of flow processing is that precise and reproducible access to well‐defined (typically very short) reaction times can be achieved by varying the respective reactor volumes or flow rates . Recently, it has been demonstrated that MOFs can be prepared with controlled particle size using flow technology . Specifically, ZIF‐8 has been produced in flow using a variety of equipment and procedures .…”
Section: Figurementioning
confidence: 99%
“…[11][12][13][14][15][16]31 Metal-organic frameworks (MOFs) are very useful crystalline hybrid porous materials, based on the coordination chemistry between metal nodes and organic ligands. [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] MOFs have attracted considerable attention in the context of various potential applications [32][33] such as gas storage, [34][35] drug delivery, 39 sensing, 40 catalysis, 38,[41][42] molecular recognition, 43 electronics 44 , separation, 45 and water-gas shift reactions, 49 due to their unique properties, such as high surface area, crystalline structure and tunable pore size. In addition, it is possible to generate chiral MOF surfaces by introducing chiral ligands.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] This kind of material not only maintains the original high melting point, low density, good dielectric properties of POSS, but also has the properties of heat resistance, pressure resistance, flame retardancy and high hardness. [23][24][25] More important, the cage structure of POSS will form nano porous in the matrix resin to reduce the dielectric constant. At present, most of the researches focus on using functional POSS to modify resin.…”
Section: Introductionmentioning
confidence: 99%